2004
DOI: 10.3184/003685004783238553
|View full text |Cite
|
Sign up to set email alerts
|

Endophytes — the Chemical Synthesizers inside Plants

Abstract: Endophytes are microbial entities that live within living tissues of plants. In most cases their relationship with the host plant is symbiotic and probably mutualistic. Many are capable of synthesizing bio-active compounds that can be used by the plant for defense against pathogenic fungi and bacteria. Some of these compounds have proven useful for novel drug discovery. By encouraging the endophytes to grow outside the plant in nutrient rich media, it is possible to harvest the bio-active compounds that they p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0
11

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(81 citation statements)
references
References 25 publications
0
70
0
11
Order By: Relevance
“…Dudeja et al (2012) states that the composition of endophytic fungi is strongly influenced by environmental and host plants. Since the host affects the production of endophytic fungal metabolites, further studies on whether the biosynthesis of active metabolite compounds continues or ceases when the fungus is grown in vitro is also necessary to know the main cause of the biosynthesis of the metabolite compound in the fungus (Owen & Hundley, 2004). The composition of endophytic fungi also depends on the interaction of pathogenic fungi and other microorganisms (Rubini et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Dudeja et al (2012) states that the composition of endophytic fungi is strongly influenced by environmental and host plants. Since the host affects the production of endophytic fungal metabolites, further studies on whether the biosynthesis of active metabolite compounds continues or ceases when the fungus is grown in vitro is also necessary to know the main cause of the biosynthesis of the metabolite compound in the fungus (Owen & Hundley, 2004). The composition of endophytic fungi also depends on the interaction of pathogenic fungi and other microorganisms (Rubini et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The discovery of novel antimicrobial metabolites from endophytes is an important alternative to overcome the increasing levels of antibiotics resistance by plant and human pathogens (17).Endophytes are chemical synthesizer inside plants (18) in additional, they play a role as a selection system for microbes to produce bioactive substances with low toxicity toward higher organisms (19).The antimicrobial activity of the endophytic bacterium B.megaterium was observed against all the tests bacteria. inhibition zones ranged between 16.5-31.0 mm against Gram-Negative Bacteria and ranged between 29.5 33.0 mm against Gram-Positive Bacteria Numbers represent average of three replicates P ≤ 0.05 observed that the scavenging activity of secondary metabolites from B .megaterium at all concentrations from 1.95 to 1000µg/ml is rather strong (20-80%).The extract improved 80%…”
Section: Resultsmentioning
confidence: 99%
“…Tan and Zou 2001;Strobel and Daisy 2003;Owen and Hundley 2004;Schulz and Boyle 2005;Gunatilaka 2006), shedding light onto selected aspects of the nature of endophytes. The aim of the hereby presented study is to render a comprehensive overview of the current knowledge on the subject.…”
Section: Introductionmentioning
confidence: 99%